EVALUATION OF THYROID FUNCTION TEST IN OBESE PATIENTS - Fathima, Faazila; P, Preetha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To evaluate thyroid function in 20-50 aged obese people. As obesity is a widespread problem today, knowledge about the factors affecting or influencing it is important. Little is known about the changes in thyroid function obese people. Influence on thyroid hormone synthesis has been proposed. Methods: Thyroid function test was done for 30 obese and 30 nonobese people, and their thyroid-stimulating hormone (TSH) levels were compared. Results: Using paired t-test, we found that there is a statistically significant difference between TSH levels in obese and nonobese people at p<0.001. Keywords: Thyroid, Obese, Nonobese, Thyroid function test.